Coberturas térmicas e convencionais para aviários matrizeiros quanto à ambiência e consumo de energia Elétrica - Oliveira, Fernando Gomes de (2013)
Brazil is a country of predominantly tropical climate, a fact that leads to uncomfortable thermal indices in most installations for poultry production. Thus, the study aimed to evaluate the thermal environment in three sections of commercial broires breedgrs houses with different coverages, and consumption of electricity in two seasons. Was used two broires breedgrs of egg production during the months of December 2012 to May 2013, located in the municipality of Rio Verde, Goiás. The experimental design was completely randomized in split plots with factorial arrangement of treatments 2x3 to evaluate sections of the fours, two models fours (thermal and conventional) and three points or sections within each fours (initial, middle and final) for 182 days, not consecutive, having the days as replicates. For analysis of energy consumption in two seasons, it was used the same design with treatments arranged 2x2, two models sheds (thermal and conventional) and two seasons (summer and autumn) having 48 days, not consecutive like repetitions. The thermal environment was assessed through thermal comfort indices: Index Temperature and Humidity, Index Temperature Black Globe Humidity, Radiation Heat Load and enthalpy, calculated by measuring the environmental variables: temperature and air relative humidity, black globe temperature, dew point, solar radiation and wind speed. Was evaluated the intake of energy through individual meters for each poultry house. The data was analyzed by SISVAR 5.1., through the analysis of variance, the Scott Knott test used to compare the means, considering a significance level of 5%. There was statistical difference between the sheds and the points assessed (P <.05). The shed thermic showed lower values for the environmental variables (Tbs and Tgn) and for thermal indices studied, however, showed larger values for the UR compared to conventional shed. Statistical difference was observed for consumption of electricity between sheds (P <0.01), but not between seasons. The conventional shed presented lower power consumption compared sheds thermic, however, the management of curtains may be influenced this result.